Debt, shame, and survival: becoming and living as widows in rural Kerala, India - Mohindra Katia; Haddad Slim; Narayana Delampady (BMC, 2012)
Abstract Background The health and well-being of widows in India is an important but neglected issue of public health and women's rights. We investigate the lives of Indian women as they become widows, focussing on the causes of their husband's mortality and the ensuing consequences of these causes on their own lives and identify the opportunities and challenges that widows face in living healthy and fulfilling lives. Methods Data were collected in a Gram Panchayat (lowest level territorial decentralised unit) in the south Indian state of Kerala. Interviews were undertaken with key informants in order to gain an understanding of local constructions of 'widowhood' and the welfare and social opportunities for widows. Then we conducted semi-structured interviews with widows in the community on issues related to health and vulnerability, enabling us to hear perspectives from widows. Data were analysed for thematic content and emerging patterns. We synthesized our findings with theoretical understandings of vulnerability and Amartya Sen's entitlements theory to develop a conceptual framework. Results Two salient findings of the study are: first, becoming a widow can be viewed as a type of 'shock' that operates similarly to other 'economic shocks' or 'health shocks' in poor countries except that the burden falls disproportionately on women. Second, widowhood is not a static phenomenon, but rather can be viewed as a multi-phased process with different public health implications at each stage. Conclusion More research on widows in India and other countries will help to both elucidate the challenges faced by widows and encourage potential solutions. The framework developed in this paper could be used to guide future research on widows.